Cr3+‐Doped Broadband NIR Garnet Phosphor with Enhanced Luminescence and its Application in NIR Spectroscopy. Issue 12 (16th April 2019) - Zhang, Liangliang; Wang, Dandan; Hao, Zhendong; Zhang, Xia; Pan, Guo‐hui; Wu, Huajun; Zhang, Jiahua
Abstract: Broadband near‐infrared (NIR) phosphor‐converted light emitting diode (pc‐LED) is demanded for wearable biosensing devices, but it suffers from low efficiency and low radiance. This study reports a broadband NIR Ca3‐ x Lu x Hf2 Al2+ x Si1− x O12 :Cr 3+ garnet phosphor with emission intensity enhanced by 81.5 times. Chemical unit co‐substitution of [Lu 3+ −Al 3+ ] for [Ca 2+ −Si 4+ ] is responsible for the luminescence enhancement and further alters the crystal structure and electronic properties of the garnet. Using the optimized phosphor, a NIR pc‐LED with photoelectric efficiencies of 21.28%@10 mA, 15.75%@100 mA and NIR output powers of 46.09 mW@100 mA, 54.29 mW@130 mA is fabricated. The high power NIR light is observed to penetrate upper arms (≈8 cm). For application in NIR spectroscopy, the NIR pc‐LED is used as light source to measure transmission spectra of water, alcohol, and bovine hemoglobin solution. These results indicate the NIR garnet phosphor to be a promising candidate for NIR pc‐LED. Abstract : Luminescence enhancement of 81.5 times is achieved in Ca3‐ x Lu x Hf2 Al2+ x Si1‐ x O12 :0.08Cr 3+ garnet phosphor by chemical unit co‐substitution. The near‐infrared phosphor‐converted light emitting diode fabricated by the optimized phosphor shows 46.09 mW output under 100 mA current and is capable of penetrating the upper arm.